Analisis Bibliometrik Klasifikasi Biaya Dalam Konteks Produksi Serta Perannya Terhadap Optimalisasi Goals Perusahaan (Literature Riview) - Khaddafi, Muammar; Nurhayati, Nurhayati; Deviani, Yola; Ananda, Suci; Kurnianto, Nugra (Ecobankers : Journal of Economy and Banking, 2024)
This article analyzes the impact of production costs and their classification on company objectives through a literature study using descriptive qualitative methods. Through a search on Google Scholar with the keywords "Production Costs and Company Goals," 25 sample articles were found from the 50 articles analyzed. The research results showed that 8 articles discussed the company's net profit, 6 articles discussed profitability, 6 articles discussed sales turnover results, 2 articles discussed increasing production results, and 3 articles discussed profit margins. The analysis found that increasing raw material costs can harm business profits, effective management of direct labor costs supports company goals, and good management of factory overhead costs can increase profitability and production efficiency. Therefore, these three cost components have a crucial role in achieving company goals, and an imbalance in their management can become an obstacle in achieving company goals.